Preliminary report on the effects of withholding salt and the effects of high and low potassium-sodium ratios upon the feedlot performance of lambs. - Hix, E.L.; Bell, T.D.; Good, A.L.; Parrish, D.B. (Kansas Agricultural Experiment Station, 2012)
Many of the feed lambs coming into Kansas have not had access to salt for several weeks and some of the lamb feeders do not add salt to their lambs fattening rations because of the possible losses in getting the lambs again accustomed to eating salt. The experimental studies, initiated this year, should indicated whether such a practice results in poorer feedlot performance. The studies should also lead to a clearer understanding of the physiological function of salt in the sheep’s diet.
Keywords: Lamb; Salt; Potassium; Sodium; Feedlot; Performance